Functionalized Silicone Elastomer via Alkaline Solution to Coat Phosphorylcholine-Based Copolymer Containing Organosilane to Improve Hemocompatibility for Medical Devices - Chou, Fang-Yu; Hara, Shintaro; Uchida, Kazuto; Matsuo, Youichi; Masuda, Tsukuru; Yokoi, Ryo; Ono, Toshiya; Anraku, Masaki; Isoyama, Takashi; Takai, Madoka (Frontiers in Materials, 2022)
Surface modification of hemocompatible copolymers on silicone elastomers (SEs) is crucial for the long-term use of medical devices. Both physical adsorption and chemical conjugation are important for modification of SE. Oxygen plasma treatment is widely used to produce silanol groups on SE for silane coupling. However, the plasma reaction is difficult to apply to the surface modification of three-dimensional complex devices. This study demonstrated an appropriate and efficient method with alkaline solution for producing silanol groups on SE for modifying phosphorylcholine-based copolymer with organosilane (cross-MPC copolymer). A 2.5 wt% aqueous solution of potassium hydroxide (KOH) was effective in producing silanol groups and for coating the cross-MPC copolymer. Additionally, we successfully modified the cross-MPC copolymer on the inner surface of SE tubes after pretreatment with the 2.5 wt% KOH aqueous solution, and the copolymer film was coated homogeneously. The cross-MPC copolymer film on SE was stable for one month under fluidic condition with a shear stress of 3.2 Pa. The hollow fiber membrane with the polymer coating inhibited blood coagulation after one week implantation with extracorporeal circulation device using a goat. Therefore, pretreatment of SE using an alkaline solution is an appropriate method for producing silanol groups for coating the cross-MPC copolymer by silane-coupling reaction.